Application of Lavender Aromatherapy and Warm Water Foot Soak Therapy in Hypertensive Patients: A Case Report - Jessika Maharani Putri; Faqih Ruhyanudin (International Journal Of Health Science, 2025)
Hypertension is a chronic increase in blood pressure that serves as one of the leading causes of cardiovascular disease and mortality in Indonesia. Management of hypertension not only focuses on pharmacological therapy but also involves non-pharmacological interventions such as complementary therapy. The combination of lavender aromatherapy and warm foot soak therapy is believed to reduce blood pressure through physiological and psychological relaxation effects. Objective: To describe changes in blood pressure among hypertensive patients after receiving a combination of lavender aromatherapy and warm foot soak therapy. Method: This study employed a case report design on Mr. E, a 52-year-old patient with mild to moderate hypertension in Balikpapan, East Kalimantan. The intervention was conducted for five consecutive days, with each session lasting 15–20 minutes. Blood pressure was measured before and after the therapy using a digital sphygmomanometer. Data were analyzed descriptively by comparing pre-test and post-test results. Results: A gradual decrease in blood pressure was observed, from 139/98 mmHg to 120/85 mmHg, with an average reduction of 19 mmHg in systolic and 13 mmHg in diastolic pressure. The patient also reported increased relaxation, reduced headache, and improved sleep quality after the intervention. Conclusion: The combination of lavender aromatherapy and warm foot soak therapy effectively reduces blood pressure through synergistic mechanisms, namely peripheral vasodilation and activation of the parasympathetic nervous system, which induce relaxation effects. This therapy can be applied as a safe, simple, and holistic complementary non-pharmacological nursing intervention to support hypertension management.